Mechanical response of masonry structure strengthened with ultra-high performance concrete (UHPC): a comparative analysis for different strengthening tactics - Jiang, Zhimei; Yang, Jun; Su, Hao (Frontiers in Materials, 2023)
Rehabilitation and strengthening of existing masonry structures can improve their safety, prolong life and save economic costs. In this study, a total of eighteen masonry column specimens strengthened by ultra-high performance concrete (UHPC) were fabricated and tested in compression. The effects of strengthening method, strengthening thickness and loading eccentricity were investigated. The failure mode, bearing capacity, strain, ductility, and energy dissipation were discussed in before and after strengthening to evaluate the UHPC strengthening effectiveness. A threedimensional numerical model established using finite element analysis (FEA) was validated with the experimental results. Results indicated that the brittle failure of masonry columns in compression could be significantly avoided using UHPC strengthening. Among three methods of strengthening, hoop strengthening was the most effective in increasing the ultimate load, ductility, and dissipated energy of masonry columns by 185.81%, 49.09%, and 297.12%, respectively. With the strengthening thickness increased from 0 mm to 20mm and 30mm, the ultimate bearing capacity of masonry columns was respectively increased by 29.17% and 117.26%, while the corresponding lateral displacement was decreased by 32.44% and 37.24%, respectively.The horizontal buckling of masonry columns can be relieved by UHPC, and the increase in eccentricity did not weaken the contribution of UHPC in strengthened masonry columns. The numerical results were in good agreement with the test results, with errors below 7.6%.